Do high CEO pay ratios destroy firm value? - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2017)
There is growing public concern over the rapid growth in CEO pay relative to average worker pay (CEO pay ratio). Critics contend that high CEO pay ratios could destroy firm value by damaging employee morale and/or signal CEO rent extraction. In this paper, we use a proprietary dataset to examine the relationship between CEO pay ratio and firm value/performance. Contrary to critics’ arguments, we find that industry-adjusted CEO pay ratios are positively associated with both firm value and performance. We also find that high CEO pay ratios are associated with higher quality acquisitions and stronger CEO turnover-performance sensitivity. Our results challenge the notion that high CEO pay ratios are on average economically harmful to the firm.